Justification of the competition strategy selection for agricultural enterprises - Bogiday, Irina (Technology audit and production reserves, 2019)
The object of research is the process of forming a competitive strategy for agricultural enterprises using the example of the «Agrotrade» Group of Companies (Kharkiv, Ukraine). One of the most problematic places of strategic management of the company is a constant analysis of the competitive environment. The process of creating a competitive strategy is associated with the systematic monitoring of changes in the external and internal environments. In the course of the research, methods of analysis, synthesis, grouping, generalization, abstract-logical, economic-mathematical and graphical methods were used. The process of determining a competitive strategy for agricultural enterprises should take into account the specifics of the industry and the functioning of the national market. It provides for the determination of one’s own competitive position and development priorities, based on benchmarking, and based on key indicators of the strategy matrix, using correlation and regression analysis, significant indicators of the consolidated financial statements of an enterprise. The rationale for the choice of indicators should be carried out using regression, it allows to determine some models and the completeness of explanatory factors. The definition of strategic performance indicators of the enterprise allows to adapt and optimize the activities of the company, to accumulate the necessary resources to achieve a specific goal. Based on the results of the analysis of the competitive environment and determining the place of the «Agrotrade» Group of Companies in it, two priority development vectors are identified, corresponding to I. Ansoff «product-market» matrix. The methods of economic and mathematical analysis make it possible to justify the feasibility of introducing a competitive strategy for the innovative development of products. A defined strategy will allow, provided that net profit is increased by at least 22.1 %, significantly improve our own competitive position and move to another, more attractive cluster, characterized by high performance indicators and based on the principles of innovative and technological development. The formation of an effective competitive strategy is a necessary component of a successful enterprise and the key to establishing a high level of industry competitiveness opens up new prospects in the international market.